2021
DOI: 10.3389/fpls.2021.717219
|View full text |Cite
|
Sign up to set email alerts
|

10Boron Is Mobile in Cowpea Plants

Abstract: Cowpea [Vigna unguiculata (L.) Walp] is cultivated in tropical and subtropical regions worldwide, but its production is usually limited by boron (B) deficiency, which can be mitigated by applying B via foliar spraying. In plants with nutrient mobility, the residual effect of foliar fertilization increases, which might improve its efficiency. An experiment was carried out to evaluate the concentration and mobility of the B isotopic tracer (10B) in different organs of cowpea plants, after the application of this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 35 publications
(50 reference statements)
1
1
0
1
Order By: Relevance
“…Leite et al [46], utilizing isotopic B labeling, provided evidence that B remobilization occurred in coffee trees, with some translocation in well-nourished plants (without B deficit), but significant phloem translocation or remobilization at a deficient supply of B, as what was reported in this research for the treatments without drought stress and without B. Olivera-Silva et al [50] demonstrated B remobilization in Cowpea (Vigna unguiculata (L). Walp), which in turn resulted in a high B accumulation and a significant increase in the dry biomass accumulation.…”
Section: B and The Biochemical Composition Of The Green Coffee Beans ...supporting
confidence: 76%
See 1 more Smart Citation
“…Leite et al [46], utilizing isotopic B labeling, provided evidence that B remobilization occurred in coffee trees, with some translocation in well-nourished plants (without B deficit), but significant phloem translocation or remobilization at a deficient supply of B, as what was reported in this research for the treatments without drought stress and without B. Olivera-Silva et al [50] demonstrated B remobilization in Cowpea (Vigna unguiculata (L). Walp), which in turn resulted in a high B accumulation and a significant increase in the dry biomass accumulation.…”
Section: B and The Biochemical Composition Of The Green Coffee Beans ...supporting
confidence: 76%
“…B acts in the biosynthesis of cell walls, assisting Ca 2+ in the deposition of pectates in cell walls. Boron also forms cis-diol-borate complexes, which are constitutional elements of the plasmalemma [50].…”
Section: Influence Of B On Coffee Productivitymentioning
confidence: 99%
“…Segundo [15] a dança é uma atividade que proporciona vários benefícios, pois melhora a capacidade respiratória, ajuda a perder peso, fortalece os músculos e diminui as dores, além de ajudar no convívio social das pessoas.…”
Section: Resultados E Discussõesunclassified